Analysis of the Quality of Licensing Management through the Online Single Submission Risk Based Approach (OSS-RBA) System at the Investment Office and One-Stop Integrated Services of Central Maluku Regency - Resya Myla Libran; Petronela Sahetapy; Aminah Bahasoan; Hendry Selanno (Syntax Idea)
This research have two purposes: 1. to learn and explain the quality analysis of licensing management through the Online Single Submission Risk Based Approach (OSS-RBA) system at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Maluku Tengah and 2. to know and explain what the supportive and impeding factors in the management of licences through the Online Single Submission Risk Based Approach (OSS - RBA) at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Maluku Tengah. The method used in this research is qualitative with a descriptive approach, using five dimensions of quality according to Parasuraman, Zeithaml, and Berry: tangibles, reliability, responsiveness, assurance, and empathy. In this research, there were 22 respondents, consisting of 7 (seven) officers at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Maluku Tengah and 15 entrepreneurs (14 UMK and 1 non-UMK). In this research, data collection techniques are carried out with observations, structured interviews, and documentation. Based on the results of the quality analysis of licensing management through the Online Single Submission Risk Based Approach (OSS-RBA) system at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Maluku Tengah. The researcher concluded the following categories of results: 1. tangibles with a good category; 2. reliability with a good category; 3. responsiveness with an excellent category; 4. assurance with an excellent category; and 5. empathy with an excellent category. In addition, there are factors that support the process of licensing management through this OSS-RBA system: ease of requirements, accessibility, rapidity of handling time, and fee/cost setting. While the factors that hinder the process of licensing management through this OSS-RBA system are: network and system connections, compliance with requirements, has not made changes to the AHU for the enterprise/AHU blocked, the entrepreneur forgot their OSS access rights, incorrectly entered KBLI, still exists the brokering practice, Identity Card Number (NIK) and Taxpayer Identification Number (NPWP) having problems and invalid